2019
DOI: 10.1007/s00299-019-02462-6
|View full text |Cite
|
Sign up to set email alerts
|

Heritability of meiotic restitution and fertility restoration in haploid triticale

Abstract: Key messageA single division meiosis mechanism of meiotic restitution is incompletely penetrant but significantly associated with restored fertility in triticale haploids (n = 21, genome formula ABR).AbstractMeiotic restitution, or failure of meiosis to produce gametes with a reduced chromosome number, can lead to the restoration of fertility in allohaploids. Meiotic restitution is of major interest for producing doubled haploids, as haploid plants undergoing meiotic restitution can often form seeds without th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 36 publications
(52 reference statements)
1
12
0
Order By: Relevance
“…Diploid meiotic mutants producing viable and unreduced ( n ≥ 2) gametes have been discovered in numerous plants [ 58 ], and although complete penetrance is extremely uncommon, it is thought to be an almost ubiquitous behavior across the entire plant kingdom [ 59 ]. Practically speaking, unreduced gametes are largely employed for polyploidization processes, and to boost the heterosis effect in several crops, including alfalfa [ 51 , 60 ].…”
Section: Candidate Genes For Unreduced Gamete Production and Exploitation Of Genomic Resources For The Analysis Of Alfalfa Meiotic Mutantmentioning
confidence: 99%
See 1 more Smart Citation
“…Diploid meiotic mutants producing viable and unreduced ( n ≥ 2) gametes have been discovered in numerous plants [ 58 ], and although complete penetrance is extremely uncommon, it is thought to be an almost ubiquitous behavior across the entire plant kingdom [ 59 ]. Practically speaking, unreduced gametes are largely employed for polyploidization processes, and to boost the heterosis effect in several crops, including alfalfa [ 51 , 60 ].…”
Section: Candidate Genes For Unreduced Gamete Production and Exploitation Of Genomic Resources For The Analysis Of Alfalfa Meiotic Mutantmentioning
confidence: 99%
“…Overall, male and female gamete production is controlled by a complex gene network, but usually n ≥ 2 eggs/pollen are the result of single gene mutations and, consequently, of a loss of protein function that may occur from early meiotic events (prophase I) to cytokinesis II [ 61 ]. In particular, when meiosis I fails to separate homologous chromosomes, we speak generally of “first division restitution” (FDR), while when meiosis II fails to separate sister chromatids, we refer to “second division restitution” (SDR) [ 59 ].…”
Section: Candidate Genes For Unreduced Gamete Production and Exploitation Of Genomic Resources For The Analysis Of Alfalfa Meiotic Mutantmentioning
confidence: 99%
“…The heritability of meiotic restitution has been described in wheat hybrids [54,67,101]. The genes for meiotic restitution in those studies originated from various accessions of durum wheat T. turgidum [65][66][67][68].…”
Section: Meiotic Restitution Does Not Increase Ploidy In Progenitors Of Octoploid Triticalementioning
confidence: 99%
“…Functional gametes in wheat-rye F 1 hybrids are formed via meiotic restitution, in which there is no pairing of chromosomes, and univalents are divided into sister chromatids in the first meiosis after which the meiosis ends [64][65][66]. It was found that meiotic restitution is genetically controlled in wheat-rye hybrids [64][65][66][67][68] and inherited in durum wheat-rye hybrids [54,66,67].…”
Section: Introductionmentioning
confidence: 99%
“…Its action relies on preventing the microtubule formation and chromosome segregation resulting in chromosome doubling [ 180 ]. The process may induce large chromosomal rearrangements [ 185 , 186 ] resulting in somaclonal variation.…”
Section: Introductionmentioning
confidence: 99%